Analysis of water balance on Lake Maninjau, West Sumatera. (August 2019) - Sunaryo; Nola, Y D; Istijono, B; Junaidi
Abstract: Lake Maninjau is located in Tanjung Raya sub-district, Agam Regency, West Sumatra Province. Geographically, it's located at 100 ° 32'46.33 "and 0 ° 50'84.2". The research was to analyze the water balance of Lake Maninjau in accordance with the rainfall data. The data used in this study was a land use map in order to determine the progress of its land cover, rainfall data, and outlet data of Lake Maninjau. The rainfall value was the value of the debit calculation input using FJ Mock, and ETo from the calculation of annual air temperature climatology data. Outflow data was obtained from a summary of the measurements of Lake Maninjau hydropower from the year of 2007 to 2017. From the analysis of water availability of Lake Maninjau, an analysis of water needs and its availability was considered sufficient to meet the water needs around the lake. It was occured when the average lake water inflow was 174, 935 m 3 /sec per year with 5, 593 m 3 /sec per year on the need for (outflow) lake water, and the difference between the two was 169, 342 m 3 /sec per year according to data from 2007 to 2017. Therefore, the capacity of Lake Maninjau's water is still requisite in number.